Group 2 Innate Lymphoid Cells in Respiratory Allergic Inflammation - Helfrich, Sofia; Mindt, Barbara C.; Fritz, Jörg H.; Duerr, Claudia U. (Frontiers in Immunology, 2019)
Millions of people worldwide are suffering from allergic inflammatory airway disorders. These conditions are regarded as a consequence of multiple imbalanced immune events resulting in an inaccurate response with the exact underlying mechanisms still being a subject of ongoing research. Several cell populations have been proposed to be involved but it is becoming increasingly evident that group 2 innate lymphoid cells (ILC2) play a key role in the initiation and orchestration of respiratory allergic inflammation. ILC2 are important mediators of inflammation but also tissue remodelling by secreting large amounts of signature cytokines within a short time period. Thereby, ILC2 instruct innate but also adaptive immune responses. Here, we will discuss the recent literature on allergic inflammation of the respiratory tract with the focus on ILC2 function. Furthermore, we will highlight different therapeutic strategies to treat pulmonary allergic inflammation and their potential influence on ILC2 function as well as the perspective of using human ILC2 for diagnostic purposes.